Can Personality Traits, Risk Attitude, and Demographics Explain Fund Managers’ Disposition Effect? - Mzioud, Omar; Meknassi, Siham (European Scientific Journal, ESJ, 2021)
This paper focuses on the extent to which personality traits, risk attitude, and demographics explain holding losses and cutting gains using survey data collected among equity and bond fund managers. For this purpose, cross-sectional multiple regressions were conducted. This paper argues that holding losses and cutting gains are two independent biases, rather than two sides of the disposition effect. The results show a significant effect of extraversion, openness, risk-taking, professional experience, and university degree on holding losses, and a significant effect of risk perception and gender on cutting gains. This paper contributes to few studies on personality traits and behavioral biases of professional investors, and it may have important practical implications in fund management companies.